Essays in applied econometrics and monetary policy - Santos, Ana Flávia Soares dos (2018)
This thesis contains three independent chapters. The first one is about central bank credibility, where we measure people’s beliefs using survey data on inflation expectations and focus on the 12-month-ahead horizon since it is widely used in the literature. Beliefs are measured by employing the panel-data setup of Gaglianone and Issler (2015), who show that optimal individual forecasts are an affine function of one factor alone – the conditional expectation of inflation. This allows the identification and estimation of the common factor, our measure of people’s beliefs. Second, we compare beliefs with explicit (or tacit) targets by constructing Heteroskedasticity and Autocorrelation Consistent (HAC) 95% asymptotic confidence intervals for our estimates of the conditional expectation of inflation, which is an original contribution of this paper. Whenever the target falls into this interval we consider the central bank credible. We consider it not credible otherwise. This approach is applied to the issue of credibility of the Central Bank of Brazil (BCB) by using the now well-known Focus Survey of forecasts, kept by the BCB on inflation expectations, from January 2007 until April 2017. Results show that the BCB was credible 65% of the time, with the exception of a few months in the beginning of 2007 and during the interval between mid-2013 throughout mid-2016. We also constructed a credibility index for this period and compared it with alternative measures of credibility. In the second chapter, we show that it is possible to conciliate individual and consensus rationality tests, by developing a new framework to test for rational expectations hypothesis. We propose a methodology that verifies the consistency of the above mentioned expectation formation rule, where we explicitly allow for the possibility of heterogeneous expectations at the individual level, but also keeping individual and consensus expectations at the same system. We advance with respect to Keane and Runkle (1990)’s previous work, which argued that almost all existing tests in the literature so far were either incorrect or inadequate. In the third chapter, we propose an individual coincident indicator for the following Latin American countries: Argentina, Brazil, Chile, Colombia and Mexico. In order to obtain similar series to those traditionally used in business-cycle research in constructing coincident indices (output, sales, income and employment) we backcast several individual country series which were not available in a long time-series span. We also establish a chronology of recessions for these countries, covering the period from 1980 to 2012 on a monthly basis. Based on this chronology, the countries are compared in several respects. The final contribution is to propose an aggregate coincident indicator for the Latin American economy, which weights individualcountry composite indices. Finally, this indicator is compared with the coincident indicator (The Conference Board – TCB) of the U.S. economy. We find that the U.S. indicator Granger-causes the Latin American indicator in statistical tests.